Rhetorical Imitation and Civic Diversity. Issue 2 (4th May 2019) - Terrill, Robert E.
ABSTRACT: The value of imitatio as a pedagogical tactic in rhetorical education has been attested to for millennia. But within the context of a culture of diversity, imitation becomes potentially problematic. This essay describes two attitudes toward imitatio that may contribute to modifying the practice in ways that enable it to be recovered for use in contemporary classrooms. The first entails reimagining the relationships between students and their model texts as multivalent conversations rather than dyadic exchanges; the second entails challenging the hierarchies that are implied when students are expected to model their work on texts that are considered superior. These two attitudes encourage the integration of imitatio into a rhetorical education that is essential for the cultivation of a just and engaged twenty-first century citizenship.